The Relationship between Policy and Social Environment and Smoking Habits among High School Students in Kolaka Regency - Aries Idi Wijayanto; Tasnim Tasnim; Andi Asri (Waluya The International Science of Health Journal, 2026)
Introduction: Smoking is one of the most difficult habits for adolescents to stop. The prevalence of smoking among students in Kolaka Regency is reported to be 48%. Smoking behavior among adolescents can be influenced by several factors, including policy and social environment. This study aims to analyze the relationship between policy and social environment and smoking habits among high school students in Kolaka Regency. Method: The study was conducted in August 2024 in three high schools in Kolaka Regency. The population consisted of 810 students, with a sample of 268 respondents selected using cluster random sampling. Data were collected using questionnaires and analyzed using the chi-square test and binary logistic regression. Result: Shows the Chi-Square test of policy (p value 0.000, ⱷ -0.401). Social environment (p value 0.000, ⱷ -0.449) on smoking habits among high school students in Kolaka district, Southeast Sulawesi Province. Conclusion: Policies and social environments are related to students' smoking habits, so schools need to hold regular outreach programs about the dangers of smoking in the form of seminars, discussions, or screenings of educational films.